A rare cause of young-onset dementia. Issue 1 (8th September 2022) - Watson-Fargie, Taylor; Davies, Rhys; Heath, Craig; Davenport, R J
Abstract : A 39-year-old woman developed progressive cognitive impairment with neuropsychiatric features, bruxism and seizures; she had a background of recurrent bony fractures. The case formed the clinicopathological conference at the Association of British Neurologists Annual meeting 2022.